BiPi-TMAC: A Bidirectional-Pipelined TDMA for Reliability and QoS Support in Tactical Unmanned Vehicle Systems - Dabin Kim; Jaebeom Kim; Young-Bae Ko (IEEE Access, 2018)
In tactical mobile ad hoc networks, unmanned vehicles such as ground maneuvering nodes or aircraft, are increasingly expected to be exploited for information collection in battlefields or dangerous areas on behalf of soldiers in consideration of their safety. The primary function of this networking system is to conduct military surveillance and reconnaissance through unmanned vehicles, which are teleoperated via a central node by sending command messages in real time. This requires simultaneous network traffic flow in both directions, i.e., uplink and downlink, both of which need to occur in real time with high reliability. In this paper, we propose a novel centralized time-division multiple access (TDMA) protocol to guarantee network reliability and quality of service regarding the bidirectional traffic. We develop a bidirectional-pipelined TDMA (BiPi-TMAC) protocol that consists of three parts: a slot-requesting procedure with bandwidth requirement, a depth-based pipelined slot allocation algorithm, and multiple MAC queue management for prioritized packet scheduling. We implement and evaluate the proposed scheme through the ns-3 simulator and show that it improves performance in terms of both uplink and downlink traffic.